Co-existing TiO2 nanoparticles influencing adsorption/ desorption of tetracycline on magnetically modified kaolin. (January 2021) - Wang, Teng; Meng, Zhaofu; Jiang, Hua; Sun, Xiuxian; Jiang, Lancui
Abstract：: Interaction of coexisting nanoparticles (NPs) and other pollutants may affect their behavior in the environment. In this study, we investigated the effects of TiO2 NPs on the adsorption and desorption of tetracycline (TC) by magnetized kaolin (MK). The interactions among TC, TiO2 NPs, and MK were then discussed through their morphology and characteristics by using scanning electron microscopy, X-ray energy dispersive spectrometry, Transmission electron microscope, X-ray diffraction, X-ray photoelectron spectroscopy, and Fourier transform infrared spectroscopy analyses. Results showed that TiO2 NPs increased TC adsorption on MK by 2.02% and increased TC desorption by 45.26%, TC increased the maximum adsorption of TiO2 on MK from 31.32 to 49.42 mg g −1 and decreased the amount of stable adsorption state TiO2 NPs on MK from 17.92 to 12.71 mg g −1 . The characterization results demonstrated that TC molecules combined on MK though hydrogen bonding, π-π bonding and hydrophobic interaction. The adsorption of TiO2 NPs on MK can provide additional hydrogen-bonding sites for TC adsorption by increasing the number of hydroxyl groups. However, TC can decrease the electrostatic attraction sites for TiO2 NPs adsorption on the MK surface. The complexation of TC and TiO2 NPs weakened the electrical attraction between MK and TiO2 NPs and decreased the amount of stable adsorption state TiO2 NPs. Graphical abstract: Image 1 Highlights: The interaction between tetracycline (TC), TiO2 nanoparticles (TiO2 NPs) and magnetized Kaolin (MK) was studied. TiO2 NPs promotes the adsorption and desorption of TC on MK. TiO2 NPs increase the TC molecules adsorbed by the hydrogen bonding on the MK surface. TC reduces the stable adsorption state TiO2 NPs on the MK surface. The increased TC desorption was related to an increase of unstable adsorption state TiO2 NPs.